The Epidemiologic Features of Acute Hepatitis B in the Saratov Region in Modern Conditions - E. V. Kouklev; L. M. Pichugina; A. I. Kologorov; A. N. Danilov; O. I. Kozhanova (Проблемы особо опасных инфекций, 2010)
Presented are the results of long-term investigations which enabled to identify the principal regularities of epidemiologic process of acute hepatitis B in modern social and economical conditions in the Saratov region. The reasons of significant morbidity decrease and the routes of infection transmission are shown. The region is differentiated as regards hepatitis B and the high priority measures on prevention of this disease are identified.